Optical Anatomy and Microscopical for the Comparison of the Olfactory Mucosa of Puppies with Lambs - Alnassiri, Shurooq Hameed Majeed; Hameed, Bader Khatlan; Ebraheem, Ayad Hameed (Journal for Research in Applied Sciences and Biotechnology, 2024)
Dogs are animal that have been used by humans for a long time in many fields because of its characteristics, which have been used in fishing, guarding, insurance, drug detection and in the field of prevention and detection of crime, The present study was done to demonstrate the histological structure and the olfactory mucosa in both lambs and puppies, so two lambs and two puppies were included in this study. The puppies were killed by using xylazine 4ml and ketamine 8ml, the lambs were already slaughtered, the nasal cavity was arrived by using the wire sow and the olfactory mucosa was immediately obtained and immersed in 10% formalin for 24 hour, then the histological technique was applied to obtain slide of 5 µm thickness and stained by haematoxylin and Eosin, and examined under light microscopic. The present result, revealed that the olfactory epithelium of the puppies was taller than in lambs and the sensory hairs was crowded in both species, also the lamina properia of the lambs showed more mucus glands continues with surface.